2020
DOI: 10.3390/medicina56120635
|View full text |Cite
|
Sign up to set email alerts
|

Cut-off Values of the Respiratory Muscle Power and Peak Cough Flow in Post-Stroke Dysphagia

Abstract: Background and objectives: This study aimed to determine the cut-off values of the following three respiratory pressure meters; the voluntary peak cough flow (PCF), maximal expiratory pressure (MEP) and maximal inspiratory pressure (MIP); associated with post-stroke dysphagia and assess which of these parameters show good diagnostic properties associated with post-stroke dysphagia. Materials and Methods: Retrospective analysis of a prospectively maintained database. Records of patients with first-ever diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…This is related to the previous study that ventilation mechanics increase in strength within two weeks of IMT (Bissett et al, 2016). The increase in respiratory muscle strength can be caused by the effects of exercise such as IMT and the MIP (Maximal Inspiration Pressure) test manoeuvre (Cabrita et al, 2021;Han et al, 2020;Tanriverdi et al, 2021) However, atrophy may occur quickly in ICU patients, especially in skeletal muscle and respiratory muscles (Spiesshoefer et al, 2020), if the patient is attached to a mechanical ventilator for more than five days. With an adequate training stimulus, the possibility of atrophy in the respiratory muscles will decrease in a relatively short period of time, so that it will help the ventilator weaning process.…”
Section: Discussionmentioning
confidence: 54%
“…This is related to the previous study that ventilation mechanics increase in strength within two weeks of IMT (Bissett et al, 2016). The increase in respiratory muscle strength can be caused by the effects of exercise such as IMT and the MIP (Maximal Inspiration Pressure) test manoeuvre (Cabrita et al, 2021;Han et al, 2020;Tanriverdi et al, 2021) However, atrophy may occur quickly in ICU patients, especially in skeletal muscle and respiratory muscles (Spiesshoefer et al, 2020), if the patient is attached to a mechanical ventilator for more than five days. With an adequate training stimulus, the possibility of atrophy in the respiratory muscles will decrease in a relatively short period of time, so that it will help the ventilator weaning process.…”
Section: Discussionmentioning
confidence: 54%
“…26,48 The difference in IEMT and EMT effects may be related to the strengthening of inspiratory muscle strength after training, which has been shown to be beneficial for their lung volume at the onset of cough. 16 Furthermore, the cough peak flow, an index of voluntary cough strength, is well correlated with maximal inspiratory pressure, in addition to maximal expiratory pressure and forced vital capacity. 49 Thus, IEMT may be more beneficial in avoiding aspiration and pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…15 Strengthening the inspiratory muscles of stroke survivors has been proven to be beneficial for their lung volume at the beginning of cough; meanwhile, the improvement of expiratory muscle strength also contributes to increased intrathoracic pressure. 16 Coughing and swallowing are highly sophisticated and interconnected re-flexive behaviors that serve to protect the airways during swallowing. Currently, positive results have been observed using IEMT in improving cough effectiveness and airway protection in neurological patients.…”
mentioning
confidence: 99%
“…The PCF cut-off value of 153 derived in this study was similar to the standard value of 160 for decannulation after tracheotomy [ 31 ]. Previous studies on patients with strokes have also revealed that dysphagia is associated with PCF, and a study by Han et al suggested a cut-off value of 151 [ 32 , 33 ]. The cut-off value of 153 in this study was similar to the PCF reference values of previous studies, suggesting clinical significance.…”
Section: Discussionmentioning
confidence: 99%